Psychological barriers to adherence to pharmacological treatment of cardiovascular risk conditions in healthcare workers - Flores-Mendoza, Jessica Berenice; Robles García, Rebeca; García-Méndez, Mirna; Rodríguez-Argüelles, Norma Liliana (Frontiers in Public Health, 2024)
Cardiovascular diseases (CVD) are the leading cause of death globally. This burden of disease is particularly high among healthcare workers (HCW). However, adherence to treatment of well-known cardiovascular risk conditions (CRC) still represents a challenge, even among healthcare workers (HCW). Since the identification of modifiable related factors is a prerequisite for developing effective public health interventions, the purpose of this study was to develop a predictive model for adherence to pharmacological treatment (APT) for CRC in HCW, using psychological variables related to CVD mortality, such as the type A behavior pattern, perceived stress, depression, anxiety and attitudes towards treatment adherence. An anonymous online survey was completed by a nonprobabilistic sample of 1,377 Mexican HCW from tertiary public hospitals, with a diagnosis of only one of the following CRC: ischemic heart disease, diabetes, high blood pressure or dyslipidemia. Sociodemographic questionnaires and self-reported measures were used to collect data: PSS-14 for perceived stress, Type A Behavior Pattern Withdrawal Scale, HADS for anxiety and depression symptoms, the Attitudes towards Medication Scale and the Therapeutics Adherence Scale for Patients with Chronic Diseases. Anxiety and depression symptoms were higher in the group with risk for non-adherence, while perceived stress and positive attitudes toward medication were higher in the group with likelihood of adherence (p≤.05). The Type A behavior pattern and sociodemographic variables did not differ between groups. In a regression model, positive attitudes toward medication and perceived stress doubled APT (OR=2.04, CI95%=1.39-2.97; OR=2.02, CI95%= 1.71-2,39, respectively) whereas depression decreased its likelihood (OR=.61,. In conclusion, psychoeducation for patients with CRC should include information on the advantages of medication for treating their condition, even if they are HCW. Promoting adaptative coping skills to handle daily stressful events, including their CRC, could reduce the level of stress that could increase their APT but also their cardiovascular risk. Moreover, our data provide evidence regarding the importance of identifying and treating depressive symptoms as part of the standard care of this population.